A novel strategy for comprehensive optimization of structural and operational parameters in a supersonic separator using computational fluid dynamics modeling - Sina Nabati Shoghl (Nature Portfolio, 2021)
Abstract In this study, the effects of several structural and operational parameters affecting the separation efficiency of supersonic separators were investigated by numerical methods. Different turbulence models were used and their accuracies were evaluated. Based on the error analysis, the V2-f turbulence model was more accurate for describing the high swirling turbulent flow than other investigated turbulence models. Therefore, the V2-f turbulence model and particle tracing model were selected to optimize the structure of the convergence part, the diffuser, the drainage port, and the swirler. The cooling performance of three line-type in the convergent section were calculated. The simulation results demonstrated that the convergent section designed by the Witoszynski curve had higher cooling depth compared to the Bi-cubic and Quintic curves. Furthermore, the expansion angle of 2° resulted in the highest stability of fluid flow and therefore was selected in the design of the diffuser. The effect of incorporating the swirler and its structure on the separation performance of supersonic separator was also studied. Three different swirler types, including axial, wall-mounted, and helical, were investigated. It was observed that installing the swirler significantly improved the separation efficiency of the supersonic separator. In addition, the simulation results demonstrated that the separation efficiency was higher for the axial swirler compared to the wall-mounted and helical swirlers. Therefore, for the improved nozzle, the swirling flow was generated by the axial swirler. The optimized axial swirler was constructed from 12 arced vanes each of which had a swirl angle of 40°. For the optimized structure, the effects of operating parameters such as inlet temperature, pressure recovery ratio, density, and droplet size was also investigated. It was concluded that increasing the droplet size and density significantly improved the separation efficiency of the supersonic separator. For hydrocarbon droplets, the separation efficiency improved from 4.6 to 76.7% upon increasing the droplet size from 0.1 to 2 µm.